The Role of Artificial Intelligence in Enhancing Sustainability: The Case of UAE Smart Cities - Khansaheb, Khulood Shebib Hussain Abdulrahman (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)